An unlikely precursor: Tchecov and Kafka - Bischof, Betina (Literatura e Sociedade, 2006)
The essay seeks, in the comparison between two narratives, one from the end of the nineteenth century and the other from the beginning of the twentieth, a clarification of the treatment each text grants certain themes: discretion, judgment without legal basis, the erosion of meaning . Through the configuration of similar motifs, the paper is interested in tracing the differences between the two works, differences that arise as answers to specific historical conditions. The works are Tchekhov's "Ward Nº.6" and kafka's The Trial.Franz